Women and ICT in Africa and the Middle East: Changing Selves, Changing Societies. Issue 1 (5th December 2017) - Addo, Atta
Abstract: Women and ICT in Africa and the Middle East: Changing Selves, Changing Societies . Edited by: Ineke Buskens & Anne Webb. Zed Books, London 2014: ISBN: 978‐1‐98360‐042‐7; £ 21.99; 326pp